Traditional vs daily undulling periodization in strength and local muscle endurance gains on trained men - Rodrigues, B. M.; Senna, G.; Simão, R.; Scudese, E.; Da Silva-Grigoletto, M. E.; Paoli, A.; Messina, G.; Bianco, G.; Bianco, A.; Dantas, E. H. M. (Journal of Human Sport & Exercise, 2018)
The aim of this study was to investigate the impact of different periodization models on strength and local muscle endurance. Twenty trained men (25.45 ± 2.984 years, 75.34 ± 6.05 kg, 177.25 ± 4.92 cm, 23.96 ± 1.64 kg . m-2) were randomly assigned in two groups: undulling periodization (UPG) and traditional periodization group (TPG), respectively. All the subjects performed one repetition maximum (1-RM) strength test and a local muscle endurance test (60% of 1-RM to failure) before, during and after experimental period. The UPG executed 30 workout sessions with daily modifications regarding intensity, volume and rest period length. The TGP was divided into 3 phases (10 workout sessions in each phase) with the same changes executed by the other group in distinct methodological variables (intensity, volume and rest period length). After the ANCOVA analysis, no significant differences were found in both maximum strength attempts, bench press (p = 0.878) and triceps pull-down (p = 0.967). The same results occurred for local muscular endurance on the bench press (p = 0.777) or triceps pull-down (p = 0.494). However, the effect size presented moderate post-test strength gains (ESs = 0,352) and local muscular endurance (ESs = 0.367). Our results indicated that daily undulling periodization seems to be more influent in increasing muscular strength and local muscular endurance according to effect size evidence.